Application of the Use Questionnaire Method in Edlink Learning Management System (LMS) Usability Measurement : Application of the Use Questionnaire Method in Measuring the Usability of the Edlink Learning Management System (LMS). - LM Fajar Israwan, LM Fajar Israwan; Rachmawati, Ike Kusdyah; Rahman Alamsyah, Agus (KH. A. Wahab Hasbullah University, 2024)
Distance education has evolved from a correspondence education model to e-learning-based education using a Learning Management System (LMS). One LMS that is widely used is Edlink. The successful implementation of an information system, including e-learning, is very important to determine the user's ability to utilise the system so that it can empirically describe e-learning user satisfaction. The purpose of this research is to measure the usability of the Edlink LMS. The questionnaire used in this research consists of the variables Usefulness, Ease of Use, Ease of Learning, and User Satisfaction. From the results of the Usability calculation, the Usefulness variable's feasibility level was 83.54%, the ease of use variable was 83.03%, the ease of learning variable was 84.79%, the usability variable was 82.62% and the total usability value was 83.31. %. This shows that LMS Edlink is a very effective learning media to use in bold learning.